Akibat Hukum Penetapan Tersangka Terhadap Orang Mati Dalam Proses Penyidikan - Serlaloy, Alfred Gilbert; Toule, Elsa Rina Maya; Salamor, Anna Maria (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2024)
Introduction: The research in this thesis is motivated by the determination of suspects regarding dead people. In Article 109 paragraph (2) of the Criminal Procedure Code, investigators must pay attention to the provisions regarding disclosure of investigations if the suspect dies. Legally, Article 77 of the Criminal Code states "the authority to demand abolition if the accused has died". the goal to be achieved is to analyze and explain whether a dead person can be designated as a suspect as well as analyze and explain the legal consequences of determining a dead person as a suspect.Purposes of the Research: The goal to be achieved is to analyze and explain whether a dead person can be designated as a suspect as well as analyze and explain the legal consequences of determining a dead person as a suspect.Methods of the Research: The research method used is normative juridical research or research to find legal rules with the approach used by the author in discussing this problem is the statutory approach.Results / Findings / Novelty of the Research: The result obtained in this writing is that the determination of a dead person as a suspect is invalid because it has violated the criminal procedural law. The legal consequences of naming 6 members of the FPI laskar and Hasya Atallah as suspects will have an impact on the good name of the suspect and also the victim's family, and efforts can be made to compensate the suspect, who can be represented by his family